Danon disease: Gender differences in presentation and outcomes. (1st July 2019) - Brambatti, Michela; Caspi, Oren; Maolo, Alessandro; Koshi, Elliott; Greenberg, Barry; Taylor, Matthew R.G.; Adler, Eric D.
Abstract: Background: Danon disease (DD) is a rare X-linked autophagic vacuolar myopathy, characterized by high penetrance and severe cardiomyopathy. Because of its rarity, the natural history (NH) is uncertain. Objectives: We aimed to describe disease variability and outcomes through a systematic review of all published DD cases. Methods: Among 83 manuscripts in MEDLINE and EMBASE on DD cases published until October 2017, we identified 146 patients with positive genetic testing for DD or positive muscle biopsy in a relative of a genetically diagnosed proband. Results: 56 females and 90 males were identified. 92.5% of patients had cardiac abnormalities. Females presented with either hypertrophic cardiomyopathy (HCM, 70.3%) or dilated cardiomyopathy (DCM, 29.3%) whereas males presented with HCM 96.2% of the time. The composite outcome of death, heart transplant or ventricular assist devices occurred equally in both sexes (32% of females and 37% of males, p = 0.60) but later in females (median age 38 years) than in males (median age 21 years, p < 0.001). Whereas women present with isolated cardiac disease 73% of the time, in males DD was frequently multisystemic and presented as a triad of cognitive impairment, skeletal myopathy, and HCM in 42% of patients. Conclusions: In this first systematic review of DD, we confirmed the severe morbidity and mortality associated with disease in both sexes. Women presented with both HCM and DCM and generally with isolated cardiac disease, whereas in men DD usually presented as HCM and was frequently multi-systemic. Further prospective NH studies will be required to confirm these findings. Highlights: The study reviewed all the case report/case series published on Danon Disease (DD). DD may be devastating in both genders. DD Males present with a triad of skeletal myopathy and cardiac and cognitive impairment. DD Females present as an isolated cardiomyopathy. DD should be considered in both sexes with clinical manifestations or positive family history.